Token Economy: A Systematic Review of Procedural Descriptions. (September 2017) - Ivy, Jonathan W.; Meindl, James N.; Overley, Eric; Robson, Kristen M.
The token economy is a well-established and widely used behavioral intervention. A token economy is comprised of six procedural components: the target response(s), a token that functions as a conditioned reinforcer, backup reinforcers, and three interconnected schedules of reinforcement. Despite decades of applied research, the extent to which the procedures of a token economy are described in complete and replicable detail has not been evaluated. Given the inherent complexity of a token economy, an analysis of the procedural descriptions may benefit future token economy research and practice. Articles published between 2000 and 2015 that included implementation of a token economy within an applied setting were identified and reviewed with a focus on evaluating the thoroughness of procedural descriptions. The results show that token economy components are regularly omitted or described in vague terms. Of the articles included in this analysis, only 19% (18 of 96 articles reviewed) included replicable and complete descriptions of all primary components. Missing or vague component descriptions could negatively affect future research or applied practice. Recommendations are provided to improve component descriptions.